2017
DOI: 10.1177/1029864917704033
|View full text |Cite
|
Sign up to set email alerts
|

Exploring emotional responses to orchestral gestures

Abstract: Research on emotional responses to music indicates that prominent changes in instrumentation and timbre elicit strong responses in listeners. However, there are few theories related to orchestration that would assist in interpreting these empirical findings. This article investigates listeners’ emotional responses to four types of orchestral gestures – large-scale timbral and textural changes that occur in a coordinated, goal-directed manner – through an exploratory experiment that collected continuous respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Similar melodic and harmonic properties, including structural transitions and alterations such as changes in tonality, were subsequently associated with MECs in several empirical studies (Auricchio, 2017; Bannister, 2020a; Bannister & Eerola, 2018; Guhn et al, 2007; Mlejnek, 2013; Schurtz et al, 2012) in addition to rhythmic properties (Schurtz et al, 2012; Solberg & Dibben, 2019), although the latter two studies lack specific detail about which rhythmic properties were involved (for a hypothesis about optimal tempo, see McEvilly, 1999). A recurrent theme is textural changes (Auricchio, 2017; Polo, 2017; Sloboda, 1991; Solberg & Dibben, 2019), particularly with the entrance of new instruments, and the alternation, contrast, or communion between solo and accompanying instruments (Auricchio, 2017; Bannister, 2020a; Bannister & Eerola, 2018; Goodchild et al, 2019; Guhn et al, 2007; Mlejnek, 2013), which are considered particularly pleasurable by listeners (Grewe et al, 2007). Voice and lyrics have also been identified as potent elicitors of MECs (Bannister, 2020a; Schurtz et al, 2012), and some researchers have identified passages from slow movements (Guhn et al, 2007) and virtuosity (Mlejnek, 2013) as possible causes of MECs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar melodic and harmonic properties, including structural transitions and alterations such as changes in tonality, were subsequently associated with MECs in several empirical studies (Auricchio, 2017; Bannister, 2020a; Bannister & Eerola, 2018; Guhn et al, 2007; Mlejnek, 2013; Schurtz et al, 2012) in addition to rhythmic properties (Schurtz et al, 2012; Solberg & Dibben, 2019), although the latter two studies lack specific detail about which rhythmic properties were involved (for a hypothesis about optimal tempo, see McEvilly, 1999). A recurrent theme is textural changes (Auricchio, 2017; Polo, 2017; Sloboda, 1991; Solberg & Dibben, 2019), particularly with the entrance of new instruments, and the alternation, contrast, or communion between solo and accompanying instruments (Auricchio, 2017; Bannister, 2020a; Bannister & Eerola, 2018; Goodchild et al, 2019; Guhn et al, 2007; Mlejnek, 2013), which are considered particularly pleasurable by listeners (Grewe et al, 2007). Voice and lyrics have also been identified as potent elicitors of MECs (Bannister, 2020a; Schurtz et al, 2012), and some researchers have identified passages from slow movements (Guhn et al, 2007) and virtuosity (Mlejnek, 2013) as possible causes of MECs.…”
Section: Resultsmentioning
confidence: 99%
“…Auricchio (2017),Guhn et al (2007),Nagel et al (2008),Polo (2017),Sloboda (1991) Increase or more frequent peaks:Bannister and Eerola (2018),Bannister (2020b),Beier et al (2020),Grewe et al (2007),Guhn et al (2007),Honda et al (2020), Nagel et al (2008) Event density High levels: Bannister and Eerola (2018), Nagel et al (2008), Polo (2017) Frequency range Expansion in high or low register: Guhn et al (2007), Polo (2017) Spectral centroid or flux High levels: Bannister and Eerola (2018) Roughness, dissonance, or fluctuation strength Increase: Bannister and Eerola (2018), Beier et al (2020), Grewe et al (2007), Nagel et al (2008), Park et al (2019) Brightness or sharpness Increase: Bannister and Eerola (2018), Beier et al (2020), Grewe et al (2007), Honda et al ), Bannister and Eerola (2018), Bannister (2020a), Guhn et al (2007), Mlejnek (2013), Schurtz et al (2012), Sloboda (1991) Rhythmic properties Schurtz et al (2012), Solberg and Dibben (2019) Textural changesIn general: Auricchio (2017),Polo (2017),Sloboda (1991),Solberg and Dibben (2019) Entrance or interplay between instruments: Auricchio (2017),Bannister and Eerola (2018),Bannister (2020a),Goodchild et al (2019),Guhn et al (2007), Mlejnek (2013) Voice and lyrics Bannister (2020a),Schurtz et al Bannister (2020a),Craig (2009),Goldstein (1980),Mlejnek (2013),Schoeller and Perlovsky (2016),Schoeller, Eskinazi, and Garreau (2018) No effect:Konečni et al (2007) …”
mentioning
confidence: 99%
“…Correspondingly, values were aligned by averaging each feature into bins per bar (on average 10 seconds). It is worth noting that acoustic features can be distinguished between compositional features and performance features 95 , where the former are represented in the musical score (such as harmony), and the latter include features that can change between performances, namely how loud and fast musicians may perform the music. Because key clarity is a compositional feature (i.e., does not change between performances), we averaged values across concert performances.…”
Section: Discussionmentioning
confidence: 99%
“…When checking for independence of features 96 , RMS and roughness correlated highly (r > .7) as did brightness and spectral centroid (r > .7) in all movements. As RMS and spectral centroid are features more commonly used compared to roughness and brightness 95,97 , and spectral centroid seems to best represent brightness 75 and overall timbral 98-100 perception, we kept only key clarity, RMS, spectral centroid, and tempo. The degree of change in these features was also obtained, that is, the difference between adjacent bars.…”
Section: Discussionmentioning
confidence: 99%
“…Similar melodic and harmonic properties, including structural transitions and alterations such as changes in tonality, were subsequently associated with MECs in several empirical studies (Auricchio, 2017;Bannister, 2020a;Bannister & Eerola, 2018;Guhn et al, 2007;Mlejnek, 2013;Schurtz et al, 2012), in addition to rhythmic properties (Schurtz et al, 2012;Solberg & Dibben, 2019), although the two latter studies lack specific detail about which rhythmic properties were involved (for a hypothesis about optimal tempo, see McEvilly, 1999). A recurrent theme is textural changes (Auricchio, 2017;Polo, 2017;Sloboda, 1991;Solberg & Dibben, 2019), particularly with the entrance of new instruments, and the alternation, contrast, or communion between solo and accompanying instruments (Auricchio, 2017;Bannister, 2020a;Bannister & Eerola, 2018;Goodchild et al, 2019;Guhn et al, 2007;Mlejnek, 2013), which are considered particularly pleasurable by listeners (Grewe et al, 2007). Voice and lyrics have also been identified as potent elicitors of MECs (Bannister, 2020a;Schurtz et al, 2012), and some researchers have identified passages from slow movements (Guhn et al, 2007) and virtuosity (Mlejnek, 2013) as possible causes of MECs.…”
Section: Musical Elicitorsmentioning
confidence: 99%